Neoplasias mamárias de cadelas: expressão gênica e proteica da via Wnt/b-catenina, sua associação com a transição epitélio-mesênquima e prognóstico - Terra, Erika Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Mammary tumors are very common in bitches and have a very similar biological behavior to the ones that occur in women, turning it an excellent model for comparative studies. Epithelial-mesenchymal transition (EMT) facilitate migration and the occurrence of metastasis, factor that have direct influence on prognosis. Thus, this study aimed to evaluate, by immunohistochemistry (IHC), EMT markers in canine mammary tumors (e-cadherin, β-catenin, vimentin and cytokeratin). In addition, gene and protein expressions of two genes WNT5A and APC were evaluated by qRT-PCR and immunohistochemistry. To this, 98 bitches with no breed or age predilection, besides normal mammary glands without neoplastic lesions were used to form four groups: (G1) 5 normal mammary samples; (G2) 28 benign mammary lesions; (G3) 56 non-metastatic mammary carcinomas and (G4) 14 metastatic carcinomas. Both genes, APC and WNT5A show higher expression between normal mammary samples and no difference among benign and malignant tumors (metastatic and non-metastatic). EMT phenotype was identified by multivariate analysis, because benign tumors were stongly associated with membranous β-catenin, high scores of Cytokeratin and no vimentin expression in epithelial cells and metastatic carcinomas were strongly associated to nuclear β-catenin, low E-cadherin expression and vimentin positivity in neoplastic epithelial cells. As nuclear localization of β-catenin is characteristic of Wnt/β-catenin signaling pathway aberrant activation, we can conclude that Wnt/β-catenin signalling pathway is activated among canine mammary tumors and EMT is occuring since benign epithelial cells have been transformed in mesenchymal cells in metastatic tumors. Those findings provide data for a better understanding of cancer progression and open new perspectives about research not only in mammary tumors, but also in other neoplastic types in dogs, facilitating to identify new prognostic factors and ...

Tumores mamários são muito comuns em cadelas e apresentam comportamento biológico semelhante aos que ocorrem nas mulheres, tornando a cadela um excelente modelo de estudo comparativo. A transição epitélio-mesênquima (EMT) facilita a migração celular, favorecendo a ocorrência de metástases, fator que tem influência direta no prognóstico das pacientes com neoplasia mamária. Assim, este estudo objetivou avaliar, pela técnica de imuno-histoquimica, marcadores de EMT em tumores mamários caninos (E-caderina, β-catenina, Vimentina e Citoceratina), além da expressão gênica e protéica de dos genes WNT5A e APC pelas técnicas de RT-qPCR e imuno-histoquímica. Para isto foram utilizadas 98 cadelas, sem predileção por raça ou idade, além de glândulas mamárias normais. Quatro grupos foram formados: (G1) 5 amostras de mamas normais sem alterações histopatológicas; (G2) 28 alterações mamárias benignas; (G3) 56 carcinomas mamários sem metástase e (G4) 14 carcinomas mamários com metástase. Ambos os genes (APC e WNT5A) mostraram maior expressão entre as mamas normais, sem diferença entre neoplasias benignas e malignas (com e sem metástase). O fenótipo de EMT foi identificado pela análise multivariada, pois neoplasias benignas foram fortemente associadas à β-catenina em membrana, escore elevado de citoceratina e negatividade para vimentina nas células epiteliais, enquanto os carcinomas metastáticos foram associados à β-catenina nuclear, baixo escore de E-caderina e positividade para vimentina em suas células epiteliais neoplásicas. Como a presença de β-catenina nuclear é característica da ativação da via de sinalização do Wnt/β-catenina, é possível concluir que esta via está ativada entre as neoplasias mamárias caninas e que o processo de EMT está ocorrendo visto a transformação das células epiteliais das neoplasias benignas em um fenótipo mesenquimal como o observado nas neoplasias ...
Keywords: Cão; Mamas - Cancer; Metastase; Imuno-histoquímica; Expressão gênica; Laminite; Immunohistochemistry